2015
DOI: 10.1163/15685411-00002863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of rhizobacterial colonisation and the ability to induce Globodera pallida hatch

Abstract: Access to the full text of the published version may require a subscription. Item downloaded fromhttp://hdl.handle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the current context of the banishment of chemical nematicides, our results could be useful for potato breeding programs and for the establishment of new biocontrol products. First, wild tuber‐bearing Solanum of clade 4 could be preferred to develop products, based on root exudates, inducing the suicide hatch of juveniles in the absence of host plant (e.g., Devine & Jones, 2000; Lettice & Jones, 2015). Second, wild tuber‐bearing Solanum from clade 3 could be used by breeders for creating new potato cultivars, which would limit hatching of cysts and thus yield losses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current context of the banishment of chemical nematicides, our results could be useful for potato breeding programs and for the establishment of new biocontrol products. First, wild tuber‐bearing Solanum of clade 4 could be preferred to develop products, based on root exudates, inducing the suicide hatch of juveniles in the absence of host plant (e.g., Devine & Jones, 2000; Lettice & Jones, 2015). Second, wild tuber‐bearing Solanum from clade 3 could be used by breeders for creating new potato cultivars, which would limit hatching of cysts and thus yield losses.…”
Section: Discussionmentioning
confidence: 99%
“…This result could be due to a differential adaptation of each G. pallida population to contrasted local climate conditions (i.e., temperature, humidity). Hence, the greatest hatching for this species occurred between 13 and 25°C Jones, 2015). Second, wild tuber-bearing Solanum from clade 3 could be used by breeders for creating new potato cultivars, which would limit hatching of cysts and thus yield losses.…”
Section: Discussionmentioning
confidence: 99%
“… Ryan and Jones (2003) demonstrated that the spontaneous hatching of potato cyst nematodes (in the absence of plant or PRE) was higher in sand compared to in vitro , suggesting the occurrence of other HF produced by microorganisms. Lettice and Jones (2015) showed that isolated rhizobacteria, including Bacillus sp. , induced higher levels of G. pallida hatching in the absence of host plant than control.…”
Section: Discussionmentioning
confidence: 99%
“…Host detection mainly occurs through a broad range of signaling molecules released by roots. Some authors suggest to use this chemical signal, as biocontrol methods, to lure the parasites and thus to decrease their population in soil, as for example, for controlling parasitic weeds ( Zwanenburg et al, 2016 ), pathogens ( Rashid et al, 2013 ; Balendres et al, 2016 ), or nematodes ( Devine and Jones, 2000a ; Lettice and Jones, 2015 ). The principle of this strategy, namely suicide hatching, is to apply hatching stimulants into the soil to induce hatching of the parasite in absence of the host plant and thus its starvation and death.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, one may be very challenging and corresponds to the development of natural biocontrol products that induce the suicide hatch of the J2s in the absence of the host plant. The "suicide hatching" concept has already been explored and some authors proposed to use it to decrease population of parasites in the soil such as parasitic weeds (Zwanenburg et al, 2016), pathogens (Balendres et al, 2016;Rashid et al, 2013) or nematodes (Devine & Jones, 2000;Lettice & Jones, 2015). In cyst nematodes, the perception of chemical cues released by the host plant is an essential prerequisite to optimize nematode chances of successful infection through the synchronization of their life cycle with the presence of the host plant.…”
Section: Introductionmentioning
confidence: 99%